Optimalisasi Pendampingan Pemilihan Material Kemasan UMKM Sambel Pecel Mbak Lina - Azdi; Hanan Fairuz Izdihar; Najwa Nur Fadilah; Akmad Farkhan; Asih Setyo Rini (Jurnal Tiyasadarma, 2026)
The snack food industry in Indonesia has transformed into a highly dynamic sector. Consumers, particularly students, tend to choose products that are practical, easy to consume, and have an attractive appearance. MSMEs are increasingly aware of the need to improve quality and hygiene by improving packaging materials. This situation has become one of the efforts to select packaging materials using the Quality Function Deployment (QFD) method. This method is used to integrate customer needs (Voice of Customer) into the product design process. Through the House of Quality (HOQ) tool, packaging attributes such as visual design, protective function, ease of use, and hygiene aspects can be identified and prioritized in a structured manner.